A standardised approach to the environmental risk assessment of potentially polluting wrecks. (May 2019) - Goodsir, Freya; Lonsdale, Jemma A.; Mitchell, Peter J.; Suehring, Roxana; Farcas, Adrian; Whomersley, Paul; Brant, Jan L.; Clarke, Charlotte; Kirby, Mark F.; Skelhorn, Matthew; Hill, Polly G.
Abstract: The potential risk to the marine environment of oil release from potentially polluting wrecks (PPW) is increasingly being acknowledged, and in some instances remediation actions have been required. However, where a PPW has been identified, there remains a great deal of uncertainty around the environmental risk it may pose. Estimating the likelihood of a wreck to release oil and the threat to marine receptors remains a challenge. In addition, removing oil from wrecks is not always cost effective, so a proactive approach is recommended to identify PPW that pose the greatest risk to sensitive marine ecosystems and local economies and communities. This paper presents a desk-based assessment approach which addresses PPW, and the risk they pose to environmental and socio-economic marine receptors, using modelled scenarios and a framework and scoring system. This approach can be used to inform proactive management options for PPW and can be applied worldwide. Highlights: National authorities are under political pressure to manage wreck oil release risk. A multi-staged risk assessment for potentially polluting wrecks is reported. Uses modelled oil release scenarios coupled with geo-spatial data to quantify risk. Facilitates prioritisation of UK wrecks and appropriate management strategies.